2012
DOI: 10.1371/journal.pone.0031819
|View full text |Cite
|
Sign up to set email alerts
|

Acute Histologic Chorioamnionitis at Term: Nearly Always Noninfectious

Abstract: BackgroundThe link between histologic acute chorioamnionitis and infection is well established in preterm deliveries, but less well-studied in term pregnancies, where infection is much less common.Methodology/Principal FindingsWe conducted a secondary analysis among 195 low-risk women with term pregnancies enrolled in a randomized trial. Histologic and microbiologic evaluation of placentas included anaerobic and aerobic cultures (including mycoplasma/ureaplasma species) as well as PCR. Infection was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 35 publications
9
84
1
1
Order By: Relevance
“…20 Others have noted a significant positive relationship between intrapartum fever and histologic chorioamnionitis in term parturients. 21,22 The authors in these studies concluded that epidural-related fever was not associated with infection but was associated with placental inflammation that was noninfectious as they noted only rare positive placental cultures. The techniques that were used for bacterial culture and identification of bacterial products by polymerase chain reaction may not have been sensitive enough or were inhibited by placental tissue in this population of term parturients.…”
Section: Discussionmentioning
confidence: 99%
“…20 Others have noted a significant positive relationship between intrapartum fever and histologic chorioamnionitis in term parturients. 21,22 The authors in these studies concluded that epidural-related fever was not associated with infection but was associated with placental inflammation that was noninfectious as they noted only rare positive placental cultures. The techniques that were used for bacterial culture and identification of bacterial products by polymerase chain reaction may not have been sensitive enough or were inhibited by placental tissue in this population of term parturients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Histological chorioamnionitis at term is most often a noninfectious inflammation; a previous study did not detect infection despite the use of robust microbiological methods. 25 Several studies have shown an association between chorioamnionitis and elevated cord serum or brain levels of proinflammatory cytokines such as interleukin (IL)-1b, IL-6, and IL-8. 25,26 Sheep models have demonstrated inflammatory responses in the fetal brain after delivery of lipopolysaccharide into the uteroplacental circulation, especially in the white matter.…”
Section: Discussionmentioning
confidence: 99%
“…25 Several studies have shown an association between chorioamnionitis and elevated cord serum or brain levels of proinflammatory cytokines such as interleukin (IL)-1b, IL-6, and IL-8. 25,26 Sheep models have demonstrated inflammatory responses in the fetal brain after delivery of lipopolysaccharide into the uteroplacental circulation, especially in the white matter. 27,28 Brain injury after chorioamnionitis leading to or in combination with HI has not been investigated as extensively, however.…”
Section: Discussionmentioning
confidence: 99%
“…CA was suspected according to clinical and biological criteria such as maternal fever (.38.5˚C), vaginal tract colonization with group B Streptococcus, prolonged membrane rupture (.18 h), high C-reactive protein, leukocytosis, and bacteriuria. The diagnosis of CA was confirmed by anatomopathological examination (21), and the CA cases were classified as grade I, grade II, and grade III, respectively, according to the progress of polymorphonuclear neutrophils from the chorion to the amnion (22). Four patients had bacteriological documentation, whereas the cultures of five patients remained negative.…”
Section: Placenta Collectionmentioning
confidence: 99%